Making Room for Alternative African Epistemologies in Ethiopian Higher Education - Debele, Meskerem Lechissa (Bahir Dar Journal of Education, 2018)
Higher education institutions in Ethiopia are expanding in diversity of fields they offer to students at the undergraduate and graduate levels. The opening and internationalization of new programs mostly responds to the demands of market forces on the one hand and the prospect of employability in the national and global market on the other as perceived by incoming students. Accordingly, curricula are mostly shaped by the interests of national and global market forces. While this is necessary to a certain extent, the need to make sure that graduates have a well-balanced regional and international outlook that goes beyond too immediate priorities of market forces should be well kept in mind by higher education program developers and curriculum designers. One issue often raised by Ethiopian scholars and others in relation to the narrow outlook of most Ethiopian higher education graduates is the fact that they are mostly unaware of (or alien to) the lives, aspirations, struggles, dreams, and achievements of people in adjacent African countries and the African diaspora. This paper is an introduction of some of the alternative and moderately influential intellectual perspectives developed by African and African-American scholars that can help balance the one-sided world outlook of Ethiopian students which is primarily shaped by the perspectives of DWEMS (â€œDead White European Malesâ€) in different fields.